2014
DOI: 10.5603/cj.a2013.0128
|View full text |Cite
|
Sign up to set email alerts
|

The long-term incidence and predictors of radial artery occlusion following a transradial coronary procedure

Abstract: Background: Radial artery occlusion (RAO) is an infrequent complication of transradial coronary procedures (TRA). (Cardiol J 2014; 21, 4: 350-356)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 24 publications
(33 reference statements)
2
13
1
Order By: Relevance
“…There are a few studies in the literature reporting radial artery diameter in the Turkish population, with mean radial artery diameter being reported as 2.3-2.8 mm. [9,10] This study's findings were similar: radial artery diameter was 2.62±0.45 mm.…”
Section: Conflict-of-interest Issues Regarding the Authorship Or Artisupporting
confidence: 70%
“…There are a few studies in the literature reporting radial artery diameter in the Turkish population, with mean radial artery diameter being reported as 2.3-2.8 mm. [9,10] This study's findings were similar: radial artery diameter was 2.62±0.45 mm.…”
Section: Conflict-of-interest Issues Regarding the Authorship Or Artisupporting
confidence: 70%
“…Since RAO is usually a thrombotic event, which is often related to the presence of micro-dissections, it is tempting to speculate that the association with occlusion time reflects a higher propensity to arterial thrombosis associated with prolonged flow impairment. Furthermore, our finding that post-procedural access site pain was also a predictor of RAO is in line with previous evidence [ 36 ], suggesting that prolonged pain after sheath removal might reflect extensive structural damage, which could in turn be a triggering for both acute thrombosis or more pronounced adverse vascular remodeling, thus leading to an increased RAO rate.…”
Section: Discussionsupporting
confidence: 92%
“…Saito et al [36] revealed severe flow reduction in patients with an A/S ratio <1. Likewise, we have also found that an A/S ratio <1 is associated with a higher incidence of long-term RAO, recently [37]. In the present study, we did not give a cutoff value for A/S ratio below which anatomical and functional changes occur because a larger study population is required to give a cutoff value to reach a statistical significance and power.…”
Section: Discussionmentioning
confidence: 60%
“…Although A/S ratio is a known predictor of radial artery patency as indicated by several studies [27][28][29], a few studies have given a cutoff value for A/S ratio for anatomical radial artery changes following TRC [36,37]. Saito et al [36] revealed severe flow reduction in patients with an A/S ratio <1.…”
Section: Discussionmentioning
confidence: 99%